Variasi Lama Waktu Kontak Tanaman Lidah Mertua (Sansevieria trifasciata lorentii mein leibling) dalam Menurunkan Kadar Karbon Monoksida dan Sulfur Dioksida di dalam Ruangan - Ramadani Sukaningtyas; Haryono Haryono; Sri Muryani (Poltekkes Kemenkes Yogyakarta, 2020)
Urban areas with a lot of industrial and technological activities, and also with densely traffic, re-sult in the increasing of air pollution. 70 % of toxic gases existed in big cities’ air are coming from motor engined vehicles. Meanwhile, the low quality of indoor air are mostly caused by internal source of contaminants. The purposes of the study were to find out the amount of carbon mono-xide (CO) and sulphur dioxide (SO2) concentration decrease after have been contacted to Lidah Mertua plants (Sansevieria trifasciata lorentii mein leibling) among 2, 4 and 6 hour variations; and to know which contact time has the most effective results. The study conducted a quasi ex-periment with controlled time series design by using a green house to observe the data. For each study group, there were five pot of the plants with equal width, height and number of leaf, and were observed from six replications. Descriptively, the results showed that the mean de-crease of CO concentration in the control and treatment groups for 2, 4 and 6 hour contact time were: 47,17 ppm (2,30 %), 120,67 ppm (5,87 %), 212,83 ppm (10,36 %); and 400,83 ppm (19,57 %), 881,50 ppm (43,05 %), 1717,50 ppm (83,88 %) respectively. Meanwhile, for SO2, the mean decrease for both groups were observed as much as 24,17 ppm (1,76 %), 62,67 ppm (4,57 %), 114,00 ppm (8,32 %); and 225,00 ppm (16,63 %), 480,00 ppm (35,48 %), 886,33 ppm (65,52 %). P-values obtained from the one way anava test were <0.001 for all the measurements. The subsequent LSD test confirmed that the highest results for the two pollutants were yielded from 6 hour contact time with mean difference of 1504,67 for CO and 772,33 for SO2.